Familles ouvrières à Montréal. Âge, genre et survie quotidienne pendant la phase d’industrialisation - Bradbury, Bettina (Boréal, 1995)
Keywords: Alimentation; Famille; Logement; Vêtements

Working Families: Age, Gender and Daily Survival in Industrializing Montreal - Bradbury, Bettina (Labour / Le travail, 1994)
Keywords: Famille; Femmes

To Love, Honour and Obey, Wife-Battering in Working-Class Montreal, 1869-1879 - Harvey, Kathryn (Université de Montréal, 1991)
Keywords: Famille; Femmes

Working Families: Age, Gender, and Daily Survival in Industrializing Montreal - Bradbury, Bettina (McClelland & Stewart, 1993)
Keywords: Famille; Femmes

To Love, Honour and Obey: Wife-Battering in Working-class Montreal, 1869-1879 - Harvey, Kathryn (Urban History Review / Revue d'histoire urbaine, 1990)
Keywords: Famille; Femmes

Le renforcement des normes sur la violence maritale. Le cas de la Montreal Society for the Protection of Women and Children, 1882-1920 - Hébert, Fernand (Bulletin d'histoire politique, 1998)
Keywords: Enfants; Famille; Femmes

Ménagères au temps de la crise - Baillargeon, Denyse (Remue-ménage, 1991)
Keywords: Crise; Famille; Femmes

Ménagères au temps de la crise - Baillargeon, Denyse (Remue-ménage, 1993)
Keywords: Crise; Famille; Femmes

Making Do: Women, Family, and Home in Montreal during the Great Depression - Baillargeon, Denyse (Wilfrid Laurier University Press, 1999)
Keywords: Crise; Famille; Femmes

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1994)
NOTICE DG
Keywords: Famille; Femmes; Travail

Maîtresses de maison dépareillées? L'apprentissage du travail domestique à Montréal au début du siècle - Baillargeon, Denyse (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1991)
Keywords: Enfants; Famille; Femmes

Making and Breaking the Rules. Women in Quebec, 1919-1939 - Lévesque, Andrée (McClelland & Stewart, 1994)
Keywords: Avortement; Famille; Femmes; Prostitution

Gender at Work at Home: Family Decisions, the Labour Market, and Girls' Contributions to the Family Economy - Bradbury, Bettina (Canadian Family History. Selected Readings, 1992)
Keywords: Enfants; Famille; Femmes; Travail

Marguerite Lacorne, conseillère de Jacques Viger - Robillard, Denise (Les Bâtisseuses de la Cité, 1993)
Keywords: Lacorne (famille); Maires; Viger, Jacques

La philanthropie et la violence maritale. Le cas de la Montreal Society for the Protection of Women and Children et de la Woman's Christian Temperance Union of the Province of Quebec - Hébert, Fernand (Université du Québec à Montréal, 1999)
Keywords: Enfants; Famille; Femmes; Philanthropie

Gender at Work at Home: Family Decisions, the labour Market and Girl's Contributions to the Family Economy - Bradbury, Bettina (Canadian and Australian Labour History. Toward a Comparative Perspective, 1990)
Keywords: Enfants; Famille; Femmes; Travail

Barbe de Boullougne ou l’ascension d’une femme dans la Nouvelle-France du XVIIe siècle - Vachon, Louise (Université de Montréal, 1999)
Keywords: Confrérie de la Sainte-Famille; Confréries

L'homosexualité masculine et les discours sur le sexe en contexte montréalais de la fin du XIXe siècle à la Révolution tranquille - Hurteau, Pierre (Histoire sociale / Social History, 1993)
Keywords: Droit; Famille; Femmes; Mariage; Médecine; Théologie